2021
DOI: 10.1007/s11747-021-00803-0
|View full text |Cite
|
Sign up to set email alerts
|

The future of buyer–seller interactions: a conceptual framework and research agenda

Abstract: The revolution in information availability and the advances in novel interaction technologies have ushered in two major shifts that call into question the traditional assumptions of buyer–seller interactions. First, buyer–seller information asymmetry has greatly decreased in many interactions. Second, face-to-face communication is no longer the main format of buyer–seller interactions. In this article, the authors review empirical research on how these shifts have changed buyer–seller ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 128 publications
0
44
0
3
Order By: Relevance
“…The existing literature on blockchains mostly implicitly refers to the characteristics of the technology that impact trust development in exchange relationships. Further, as Ahearne et al (2021) showed, technology-facilitated buyer-seller interactions are another important area on the future research agenda, and this includes blockchain-enabled exchanges. Thus, there is more than enough momentum to address the characteristics of blockchain exchanges from the perspective of the established literature of trust in B2B relationships to understand how marketers can successfully adopt blockchain in their businesses.…”
Section: Concluding Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The existing literature on blockchains mostly implicitly refers to the characteristics of the technology that impact trust development in exchange relationships. Further, as Ahearne et al (2021) showed, technology-facilitated buyer-seller interactions are another important area on the future research agenda, and this includes blockchain-enabled exchanges. Thus, there is more than enough momentum to address the characteristics of blockchain exchanges from the perspective of the established literature of trust in B2B relationships to understand how marketers can successfully adopt blockchain in their businesses.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Thus, the rich contributions stemming both from the calculative perspective (Williamson, 1993) and the relational perspective (e.g., Moorman et al, 1993) on trust are mostly about the history of people trusting people or organizations at different levels (e.g., Fang et al, 2008). However, as Ahearne et al (2021) recently showed, buyer-seller interactions facilitated by technology are fundamentally transforming the landscape of exchange relationships. Therefore, revolutionary technologies such as blockchain will presumably also change exchange relationships and, accordingly, also the development of trust, which is a key component in business relationships.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies about communication content and the linguistic assessment of communication could focus on oral communication-for example, through direct observation and video recordings (Ahearne et al, 2022;Choudhury et al, 2019). Researchers might observe project meetings to learn about the influence of oral communication on how project parties reach, or not, a consensus about adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Communication is touted as the "glue" that holds parties together in interorganizational projects (Mohr & Nevin, 1990, p. 36) by facilitating the transmission of persuasive information (Ahearne et al, 2022;Paulraj et al, 2008). The importance of communication is also mentioned as part of relational contracting (Heide & John, 1992;Zhou et al, 2014), but the role of communication in adaptation to disruptions in interorganizational projects is little-studied in that literature.…”
Section: Conceptual Backgroundmentioning
confidence: 99%